Participatory methods for planning the future in forest communities - Evans, K.; Jong, W. de; Cronkleton, P.; Nghi, Tran Huu (2010)
Forest devolution and government decentralization have increased community control over forests. Remoteness, low literacy, and lack of formal planning experience often leave forest communities unprepared for their new responsibilities. Forest communities need to develop skills that allow them to establish goals and make decisions transparently and democratically and to negotiate effectively with other local actors if they are to become more proactive participants in local governance processes. In Bolivia and Vietnam we tested four adaptations of scenario-based methods to assist forest communities to develop these skills. This article reflects on the strengths, limitations, and new applications of these methods. The methods encourage participation by members who have little experience with structured planning, including the most marginalized: women, elderly, and illiterate participants. The methods are useful as planning tools, for generating records of decisionmaking processes, and for preparing for negotiations between communities and local governments